2014
DOI: 10.1016/j.eurpsy.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Role ofDRD2andALDH2genes in bipolar II disorder with and without comorbid anxiety disorder

Abstract: The presence of comorbid anxiety disorders (AD) and bipolar II disorders (BP-II) compounds disability complicates treatment, worsens prognosis, and has been understudied. The genes involved in metabolizing dopamine and encoding dopamine receptors, such as aldehyde dehydrogenase 2 (ALDH2) and dopamine D2 receptor (DRD2) genes, may be important to the pathogenesis of BP-II comorbid with AD. We aimed to clarify ALDH2 and DRD2 genes for predisposition to BP-II comorbid with and without AD. The sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…In agreement, A1-allele carriers display higher levels of childhood antisocial behavior, bipolar disorder with low anxiety, impulsivity, novelty/stimulus seeking, aggression, antisocial/borderline traits, faster habituation to positive feedback (decoupling behavior from experience), and substance abuse/dependence but also adaptive traits such as extraversion, behavioral activation, low depression or harm avoidance, and improved cognitive performance (Noble et al, 1998;Bartrés-Faz et al, 2002;Eisenberg et al, 2007;Hoenicka et al, 2007;Ponce et al, 2008 ;Althaus et al, 2009;Esposito-Smythers et al, 2009;Ponce et al, 2009;Barskiĭ et al, 2010;Nemoda et al, 2010;Smillie et al, 2010;Stelzel et al, 2010;Thaler et al, 2012;Kazantseva et al, 2011;Lu et al, 2012;Zai et al, 2012;Wang et al, 2013aWang et al, , 2014. A1-carriers also showed significantly lower levels of risk for depression and higher engagement bias towards positive social stimuli, thus evincing a more stable and higher DA functioning (Elovainio et al, 2007;Gong et al, 2013).…”
Section: Da Receptor Configuration (D2-receptors)mentioning
confidence: 74%
“…In agreement, A1-allele carriers display higher levels of childhood antisocial behavior, bipolar disorder with low anxiety, impulsivity, novelty/stimulus seeking, aggression, antisocial/borderline traits, faster habituation to positive feedback (decoupling behavior from experience), and substance abuse/dependence but also adaptive traits such as extraversion, behavioral activation, low depression or harm avoidance, and improved cognitive performance (Noble et al, 1998;Bartrés-Faz et al, 2002;Eisenberg et al, 2007;Hoenicka et al, 2007;Ponce et al, 2008 ;Althaus et al, 2009;Esposito-Smythers et al, 2009;Ponce et al, 2009;Barskiĭ et al, 2010;Nemoda et al, 2010;Smillie et al, 2010;Stelzel et al, 2010;Thaler et al, 2012;Kazantseva et al, 2011;Lu et al, 2012;Zai et al, 2012;Wang et al, 2013aWang et al, , 2014. A1-carriers also showed significantly lower levels of risk for depression and higher engagement bias towards positive social stimuli, thus evincing a more stable and higher DA functioning (Elovainio et al, 2007;Gong et al, 2013).…”
Section: Da Receptor Configuration (D2-receptors)mentioning
confidence: 74%
“…Heroin-dependent ALDH2*2 individuals also had higher risk-taking scores compared to controls with the same genotype (24). Another study suggested that ALDH2*2 may protect against developing bipolar disorder (25). …”
Section: Impact On Human Healthmentioning
confidence: 99%
“…Wang et al [111] provided preliminary evidence that comorbid BP-II +AD might be one of the subtypes of BPII. The DRD2 gene could be an important candidate gene for the comorbidity of AD in other mental illness and ALDH2 gene might moderate the impact of DRD2 gene on BPII with or without AD.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [111] revealed the relationship among DRD2 gene and ALDH2 gene between BP with and without AD and found, we examined whether the DRD2 and ALDH2 genes were associated with comorbid BP-II and AD. The study results revealed the significant association of DRD2 Taq-IA A1/A2 in the BP-II with AD and the significant interaction between the ALDH2 and DRD2 genes in BP-II without AD, respectively.…”
Section: The Drd2 Gene Associated With Aldh2 In Bipolar II Disorder Wmentioning
confidence: 99%